Changes in metabolic energy measures for daily living activities and exercise in men and women following arduous activity in Antarctica - John Hattersley; C. Doug Thake; Chris Imray; Adrian J. Wilson (PLoS ONE, 2025)
This study reports pre- to post-expedition (pre|post) changes in energy expenditure and substrate utilisation during daily living activities (DLAs including rest, sleep, modest exercise, sedentary work and leisure) and maximum aerobic power ( V ˙ O2max ) for participants in the Inspire-22 expedition (6 men, 3 women) who undertook a 47 day unassisted Antarctic traverse from the Ronne Ice Shelf to the South Pole. DLA measurements were carried out during a 36 hour study in a whole-body calorimeter whilst measurements of maximum oxygen uptake ( V ˙ O2max ), capillary glucose and lactate during incremental stepping exercise to volitional exhaustion were carried out under normobaric normoxic and hypoxic (14% O2) conditions in an environmental chamber. Non-exercise measures were normalised to non-fat tissue weight; exercise measures, including those in the DLAs, to body weight. Statistical analysis used the Aligned Rank Transform (ART) non-parametric ANOVA technique with covariants pre|post expedition, sex and hypoxia|normoxia as appropriate. There were no systematic differences between pre- and post-expedition energy expenditure but significant differences between men and women for the majority of the DLAs (p < 0.05). There was increased carbohydrate utilisation post-expedition for sleep and the two lower intensity exercise levels (p < 0.05) but not during rest or the highest intensity exercise (p > 0.05); a sex-independent subset of 4 showing much higher utilisation. Women had a lower protein utilisation than men during the DLA exercise activities (p < 0.05). V ˙ O2max was lower in hypoxia than normoxia (p < 0.001) and reduced glucose and lactate between pre- and post-expedition measures. There was also a significant interaction between sex and pre|post measurements for V ˙ O2max and lactate suggesting that adaptation to the environment and high workloads was different between men and women; a suggestion supported by the difference in fat-free tissue measured pre- and post-expedition, but neither sex showed major differences between the pre- and post-expedition measurements.